ENVIRONMENTAL AWARENESS MOVEMENT TO REDUCE ENVIRONMENTAL IMPACTS ON HEALTH IN PP. AL FITRAH AS-SALAFIYAH SURABAYA - Suwito, Bambang Edi; Irawan, Danny; Kartini, Yanis; Rizki, Lailatul Khusnul; Muhammad, Akbar reza (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
Environmental health is essential in community-based health, prioritizing preventive and promotive efforts. A lousy environment has the potential to cause the emergence of various diseases, especially in Islamic boarding school environments. This community service aims to create an environmental awareness movement among Islamic boarding school students and female students to reduce the environmental impact on health in PP. Al Fitrah Assalafiyah Surabaya. This community service uses a descriptive analysis approach. PKM partners are 40 PP students and female students. PP. Alfitrah Assalafiyah Surabaya. Activities involve a lecture, discussion, and question-and-answer approach. As a result of community service, it is known that students can follow counseling well from start to finish. A total of 40 students arrived on time and actively asked questions and discussed. At the end of the event, a symbolic handover of recyclable waste bins was carried out as a symbol of the environmental awareness movement for Islamic boarding school students and female students. The conclusion is that students can understand the importance of environmental awareness movements after being given conclusions helpful in maintaining the health and comfort of students at the Al Fitrah Assalafiyah Surabaya Islamic boarding school.